2023
DOI: 10.1186/s12879-023-08354-1
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of hepatitis viral infections among sanitary workers across worldwide: a systematic review and meta-analysis

Sina Tolera,
Dechasa Adare Mengistu,
Fekade Ketema Alemu
et al.

Abstract: Background Sanitation or sanitary workers are exposed to hepatitis virus infections because of filthy and dangerous working conditions. The current global systematic review and meta-analysis aimed to estimate the pooled sero-prevalence of occupationally associated hepatitis virus infection among them. Methods Preferred Reporting Items for Systematic Reviews (PRISMA), and Population, Intervention, Comparison, Outcome and study design (PICOS) were us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A meta-analysis done in 2023 showed that the overall pooled seroprevalence of HAV infection among waste collectors across the world was 56.7%. While 22.6% and 22.8% for HBV and HCV respectively (5) . There were no HIV positive personnel in the current study and that was consistent with Beni Suef MSW workers (0%) (21) , Sanaa', Yemen medical waste handlers in hospitals (0%) (24) and Brazil garbage recycling cooperatives workers 0.75% (3) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A meta-analysis done in 2023 showed that the overall pooled seroprevalence of HAV infection among waste collectors across the world was 56.7%. While 22.6% and 22.8% for HBV and HCV respectively (5) . There were no HIV positive personnel in the current study and that was consistent with Beni Suef MSW workers (0%) (21) , Sanaa', Yemen medical waste handlers in hospitals (0%) (24) and Brazil garbage recycling cooperatives workers 0.75% (3) .…”
Section: Discussionmentioning
confidence: 95%
“…They may become infected with the Hepatitis A Virus (HAV) and salmonellosis through contact with garbage that has been contaminated with infectious faeces. The activation of the fecal-oral pathway by poor sanitation and improper work practices like smoking or eating while working without following proper hygi-enic precautions may increase the risk of HAV virus and salmonella transmission (5,6) Aim of the study: This study aims to identify the frequency of some infectious diseases among Minia waste collectors which are HCV, HBV, HAV, HIV and salmonellosis. Investigating the relationship between these diseases and the workers' work ability was another aim for this study.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of the review question are clearly defined by the development of exclusion and inclusion criteria based on the PICOS format. (32) Application in the meta-analysis three steps need to be done, namely among them: (33) 1. Determine the problem formulation of research in PICOST In this step, the formulation of meta-analysis research problems is carried out by determining PICOST (population, intervention, comparison, and outcome).…”
Section: Discussionmentioning
confidence: 99%